Tourism Development in Northeast Langkawi: The Views From Within - Wan Hin, Tan (Malaysian Journal of Science, 2005)
Tourism has been aggressively developed in Langkawi since the late 1980s. However, the number of tourists has stagnated and new attractions are necessary. Accordingly, the relatively undeveloped Northeast of Langkawi with its natural resources can help revitalise the tourism industry through ecotourism. The paper examines the perceptions of local residents towards the economic, social and environmental effects associated with tourism development. Ecotourism development is viewed positively by the residents. They perceived that ecotourism will bring about economic benefits to the area though disbenefits such as inflation may arise. It is unlikely to cause social or environmental problems as ecotouristic activities involves small number of tourists, occur far away from area of population and cause little disruption to the environment.